Prognostic value of copeptin in patients with acute pulmonary thromboembolism - Deveci, Figen; Oner, Onsel; Telo, Selda; Kirkil, Gamze; Balin, Mehmet; Kuluozturk, Mutlu (Wiley, 2019)
Background and Aims The aim of this study was to determine the level of copeptin, which is one of the new cardiac markers in acute pulmonary thromboembolism (PE) cases, and to determine the relationship between the severity of the disease, risk classification and hospital, first month, third month and 3-month total mortality. Methods The study included 100 cases with PE and 60 healthy control subjects. Copeptin was measured in control group. The risk grade of the cases was determined according to the sPESI index. Patients survival data at the first and third months were determined. This study was performed in patients with strict exclusion criteria for comorbidities known to be associated with increased risk of PE. Results sPESI was >= 1 in 68 (68%) of patients with acute PE. Mean serum copeptin levels were found statistically higher in patients with high risk compared to low-risk cases and controls (9.18 +/- 3.29, 6.47 +/- 2.29, and 5.26 +/- 2.15, P < 0.0001, respectively). When the cut-off value of copeptin was taken as >= 7.87 with ROC analysis for predicting high sPESI score, the sensitivity of the copeptin was 78% and the specificity was 62% (AUC = 0.74, 95% CI = 0.63-0.85, P < <0.0001). When cases divided in the groups according to the cut-off value as 7.87, first month hospital mortality and 3-month total mortality rate was found statistically higher in patients with copeptin >= 7.87 (chi(2) = 5.33 P < 0.05, chi(2) = 3.88, P chi(2) = 4.26, P < 0.05 respectively). Conclusions The results of our study showed that increased serum copeptin levels might predict the severity of PE as well as a promising marker of early mortality in high-risk cases according to sPESI.
Keywords: copeptin; mortality; pulmonary embolism; sPESI